EXTRACTION OF ECTOPIC MAXILLAR THIRD MOLARS AFTER CONE BEAM COMPUTED TOMOGRAPHY SURGICAL PLANNING: A CASE REPORT - Brzakov, Riste; Nikolovski, Bruno; Radojkova, Vera Nikolovska; Dimova, Cena (Journal of Morphological Sciences; Vol 4 No 1 (2021): JMS, 2021)
Intraoperative imaging is increasingly used by surgeons and has become an integral part of many surgical procedures. Ectopically impacted third molars in the upper jaw, become a common developmental abnormality. Surgical planning of a case with bilaterally impacted maxillary teeth by using cone beam computed tomography is presented. The 3D model provide valuable information for improved diagnosis and treatment plan and ultimately results in more successful treatment, as in the present case. The surgeon, knowing the precise location of the tooth and shape of roots in all projections would reduce the invasiveness of surgery. This report describes a case of impacted upper wisdom teeth without any associated pathologic condition. Keywords:  Third Molar; Ectopic Molar, Maxillary Sinus; Headache; Cone Beam Computed Tomography https://doi.org/10.55302/JMS2141113b